Differential Regulation of the Immune Response in the Spleen and Liver of Mice Infected with Leishmania donovani - Rashmi Bankoti; Simona Stäger (Journal of Tropical Medicine)
Immunity to pathogens requires generation of effective innate and adaptive immune responses. Leishmania donovani evades these host defense mechanisms to survive and persist in the host. A better understanding and identification of mechanisms that L. donovani employs for its survival is critical for developing novel therapeutic interventions that specifically target the parasite. This paper will highlight some of the mechanisms that the parasite utilizes for its persistence and also discuss how the immune response is regulated.